Modelling the age dynamics of chronic health conditions: Life-table-consistent transition probabilities and their application - Frank T. Denton; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2011)
We derive transition probability matrices for chronic health conditions using survey prevalence data. Matrices are constructed for successive age groups and the sequence represents the age dynamics of the health conditions for a stationary population - the probabilities of acquiring the conditions, of moving from one chronic conditions state to another, and of dying. One can simulate the life path of a cohort under the initial probabilities, and again under altered probabilities to explore the effects of eliminating a particular condition or reducing its mortality probabilities. We report the results of such simulations and note the general applicability of the methods.
Keywords: I19; J19; 330; Chronic health conditions; Transition probabilities; Age dynamics